Analisis Faktor Penghambat Utama Adopsi Quick Response Code Indonesian Standard (QRIS) di Indonesia: Pendekatan Systematic Literature Review (SLR) - Aura Rismayani Syaharin; Mochammad Andre Agustianto (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2025)
This study aims to analyze the main factors inhibiting the adoption of the Indonesian Standard Quick Response Code (QRIS) in Indonesia through a Systematic Literature Review (SLR) approach of ISSN/E-ISSN publications for the 2020–2025 period. The study focused on two central issues: the lack of public understanding of QRIS, reflected in low digital and financial literacy, and the strong habit of using cash for transactions, particularly among MSMEs. The study results indicate that gaps in understanding how QRIS works, its benefits, and its security, the need for daily liquidity, concerns about the settlement process, and a higher level of trust in cash are the dominant barriers to adoption. Contextual factors such as limited digital infrastructure, technical challenges with scanning and networking, and concerns about transaction security reinforce these two main barriers and reduce perceptions of usefulness and ease of use, according to the TAM and SDG frameworks. This study recommends more intensive and targeted policy interventions, outreach, training, and education, along with strengthening digital infrastructure, to accelerate QRIS adoption and support the creation of an inclusive and sustainable cashless transaction ecosystem in Indonesia.